Moving Forward After COVID‑19: New Directions for Teaching and Course Design in Higher Education - Naffi, Nadia; Davidson, Ann-Louise; Winer, Laura; Beatty, Brian; Germain-Rutherford, Aline; Diab, Rula; Focarile, Teresa; Rukavina, Danny; Hornsby, David; Strickland-Davis, Shantell; Boujaoude, Saouma; Côté, Stéphanie; et al. (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2023)
This study identifies course design practices and evaluation strategies that promote high-quality, equitable, and inclusive education in hybrid or online modalities, and that consider student well-being and mental health, for the post-pandemic era. Our data set consisted of an integrative literature review, interviews with instructors, and focus groups with teaching and learning centre representatives from five countries: Canada, the United States, the United Kingdom, France, and Lebanon. The study informs instructors’ professional development, recommends concrete course design elements that promote equitable education, and shares innovative pedagogical practices for digital contexts.